Kajian Hukum Terhadap Status Kepemilikan Tanah di Sulawesi Tenggara - Melissa Arifin; Benny Djaja (LPPM Universitas Ekasakti Padang, 2023)
and has a very significant role and value in human life, which is reflected in the many land conflicts that have existed in various forms and contexts throughout history. This research applies a legal and sociological approach, using an interactive analysis model. The research results show that land conflicts in society are very diverse, including inheritance disputes, grants, and land buying and selling transactions. Factors that trigger land conflicts generally include the high economic value of land, increasing public awareness, increasing population, and the problem of poverty. In general, resolving land conflicts in society can be divided into two approaches, namely through court processes (litigation) and outside the court (non-litigation). Out-of-court settlements that are generally applied by the community include various methods, such as negotiation involving interested parties, mediation involving an independent third party as a mediator, and facilitation involving more than two parties to find a joint solution.